First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.